(untitled) (Academicia Globe: Inderscience Research, 2023)
In this study, four compounds that are pyrrolidine-2,5-dione derivatives were synthesized. The reaction between N-substituted maleimide and aryl hydrazide (benzohydrazide, N-phenylhydrazine carboxamide or isonazide) produced novel compounds (K1, K2, K3 and K4). The pyrrolidine-2,5-dione derivatives were identified using FT-IR, 1H- and 13C-nuclear magnetic resonance (NMR), mass spectrometry, and the melting point of the prepared compounds. The MTT test was used to investigate four substances with anti-breast cancer (MCF-7) .